الرضا الوظيفي لدى العاملين بجامعة بنغازي - أمينة آدم المسماري; ناصر محمد أمعيتيق; عبدالسلام مراجع معتوق (Scientific Journal of University of Benghazi, 2018)
The study described in this paper addresses the measurement of job satisfaction level of the employees of the University of Benghazi in terms of salary, rewards and promotions, work duties and responsibilities, relationship between leadership and their subordinates, and appreciation and self-esteem. It also investigates the extent of the independent variables (gender, age, experience, qualification and job title) on job satisfaction and whether there are any significant differences in job satisfaction that attributed to these independent variables. The sample of this study included 176 employees distributed over the different faculties, departments and centres in the main campus of the University of Benghazi. The questionnaire-based approach has been used as research instrument for gathering data from the participants. Appropriate statistical methods have been used to analyse data, which include: calculating frequencies, arithmetic mean, standard deviation, T-test and one way analysis of variance (ANOVA). The results indicated that the level of employees’ job satisfaction was “Moderate” with arithmetic mean and standard deviation as 3.05 and 1.22, respectively. The results have also indicated that there were no significant differences in job satisfaction regarding to age, gender, experience, and job title at 0.05 significant level, whereas, there was a significant difference in job satisfaction regarding the qualification at 0.05 significant level. Finally, recommendations and suggestions were given in light of the results obtained. The present study was conducted in 2012, and the authors look forward to re-conducting it in the near future and comparing the results with those of the present study in order to analyze the change in the job satisfaction level for the employees of the University of Benghazi over time.